Research on the Development Status of China's Renewable Energy Industry - The Impact of Capital Structure on Company Performance - Wei, Xinyang; Che, Hongyi; Sheng, Ni; Hsiao, Cody Yu-Ling; Tong, Qing; Yan, Gaoyun (Frontiers in Energy Research, 2020)
China's renewable energy industry has developed rapidly. However, due to China's current energy structure, coal plants still dominate the power generation, which poses a huge challenge to China's greenhouse gas reduction. On the other hand, this situation indicates that China's renewable industry still has great development potential and the sector can make a constructive contribution to China's response to climate change. However, in the process of developing the renewable sector, how to improve the profitability of enterprises and gradually lower the dependence on traditional energy is an important issue faced by corporate and government decision-makers. Therefore, from the perspective of capital structure, this paper aims to study its impact on the performance of renewable companies in China so that the society can achieve a “win-win” situation for enterprise development as well as environmental protection. By using pooled ordinary least squares and advanced panel data models, including fixed effects model and random effects model, the empirical results show that the relationship between capital structure and company performance is statistically significant in China's renewable industry. Specifically, the sustainable growth rate is significantly positively correlated with the total net profit margin, indicating that the sustainable growth model can be used to estimate the profitability of renewable companies in China.